1990
DOI: 10.1038/sc.1990.11
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between heart rate and oxygen uptake in thoracic level paraplegics

Abstract: SummaryIn able-bodied subjects heart rate and oxygen uptake have a linear relation up to submaximal workloads. Cardiac response to exercise or physical stress is described to be under the control of the sympathetic nervous system. Various workers have claimed that the sympathetic contribution to the cardiac plexus arises between thoracic spinal cord levels Tl and T6. Paraplegics are participating in various sporting activities in increasing numbers. Theoretically, assessing the progress of physical fitness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 7 publications
2
21
0
Order By: Relevance
“…27 ± 32 In fact, Irizawa et al 33 demonstrated that, during arm crank exercise, the higher the level of the SCI lesion, the higher the HR at a given VO 2 . The HR response to increased VO 2 during CFES LE was less dramatic in our subjects compared to the results of Bar-On et al, 26 which con®rm the di culties in using HR as a measure of intensity during upper body exercise in the SCI individual. Our ®ndings are meaningful in that the subjects demonstrated a relationship between exercise intensity induced by arti®cial stimulation and an increase in HR, that this relationship was more consistent after training, and was retained following DT.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…27 ± 32 In fact, Irizawa et al 33 demonstrated that, during arm crank exercise, the higher the level of the SCI lesion, the higher the HR at a given VO 2 . The HR response to increased VO 2 during CFES LE was less dramatic in our subjects compared to the results of Bar-On et al, 26 which con®rm the di culties in using HR as a measure of intensity during upper body exercise in the SCI individual. Our ®ndings are meaningful in that the subjects demonstrated a relationship between exercise intensity induced by arti®cial stimulation and an increase in HR, that this relationship was more consistent after training, and was retained following DT.…”
Section: Discussionsupporting
confidence: 50%
“…Bar-On et al 26 reported that the HR-VO 2 relationship is linear for both paraplegic and quadriplegic subjects during arm ergometry. However, their data cannot be compared to HR-VO 2 changes during CFES LE by the SCI individual given the variable magnitude of peripheral pooling of blood and resulting impairment to venous return during upper body exercise in the SCI individual.…”
Section: Discussionmentioning
confidence: 99%
“…The excluded subject had a higher energy consumption with a low heart rate, probably due to the damage of the spinal centre of sympathetic regulation of heart, according with the observation of Bar-On and Nene. 23 The high level of heart rate of subjects walking with ARGO indicates a considerable e ort and can be explained considering that normally at a comparable oxygen uptake the heart rate is greater in arm work than in leg work. 24 Also paraplegics performing a graded arm exercise show an unusually low increase of stroke volume.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The guidelines of the American College of Sports Medicine (ACSM) for training of able-bodied persons -50-85% heart rate reserve (HRR) 5 -have also been applied in training studies with persons with paraplegia (PP) 6 as well as tetraplegia (TP). 7,8 These guidelines may be valid for persons with PP, as several studies [9][10][11][12][13][14] showed a strong individual linear HR-VO 2 relationship in persons with PP. In individuals with TP however, this may be different as a result of the disturbed sympathetic innervation, which may affect the HR-VO 2 relationship.…”
Section: Introductionmentioning
confidence: 99%
“…9,10,12,14 Moreover, only a few studies have focused on the HR-VO 2 relationship in persons with TP 13,20,21 and only one focused on the individual relationship. 20 The available studies all use hand rim wheelchair or arm crank exercise to investigate the HR-VO 2 relationship.…”
Section: Introductionmentioning
confidence: 99%